Accounting for risk aversion, income distribution and social welfare in cost‐benefit analysis for flood risk management. (9th December 2016) - Kind, Jarl; Wouter Botzen, W.J.; Aerts, Jeroen C.J.H.
Abstract : Most cost‐benefit analysis (CBA) textbooks and guidelines recognize the objective of CBAs to improve social welfare—a function of well‐being of all individuals, conceptualized by utility. However, today's common practice to value flood risk management benefits as the reduction of the expected annual damages does not comply with this concept of social welfare, since it erroneously focuses on money instead of well‐being (utility). Diminishing marginal utility of money implies that risk aversion and income differences should be taken into account while calculating the social welfare benefits of flood risk management. This is especially important when social vulnerability is high, damage compensation is incomplete and the distribution of income is regarded as unfair and income is not redistributed in other ways. Disagreement, misconception, complexity, untrained professionals, political economy and failing guidance are potential reasons why these concepts are not being applied. Compared to the common practice, a theoretically more sound social welfare approach to CBA for flood risk management leads to different conclusions on who to target, what to do, how much to invest and how to share risks, with increased emphasis on resiliency measures for population segments with low income and high social vulnerability. The social welfare approach to CBA, illustrated in this study in the context of floods, can be applied to other climate risks as well, such as storms, droughts, and landslides. WIREs Clim Change 2017, 8:e446. doi: 10.1002/wcc.446 This article is categorized under: Climate Economics > Iterative Risk‐Management Policy Portfolios Abstract : Welfare economics does often not support the practice to value risk reduction benefits on basis of expected annual damages, since this ignores risk aversion and income differences. Cost‐benefit analysis based on social welfare would lead to increased emphasis on resiliency measures for populations which are poor or socially vulnerable.